Improved Tank in Series Model for the Planar Solid Oxide Fuel Cell - Hosseini, Shahin; Danilov, Valery; Vijay, Periasamy; Tade, Moses (American Chemical Society, 2011)
Models of different complexity are required in the iterative process of designing a solid oxide fuel cell (SOFC). Models having less complexity and computational dexterity are the ideal ones at the early stages. This work presents the development of an improved tank in series reactor model of the SOFC operating in cocurrent, countercurrent, and cross-current flow directions. The model, which accounts for the charge balances in the electrodes and electrolyte in addition to the component balances and the energy balances, is used for simulating the potentiostatic operation of the cell. The simulation results from the TSR model indicate the influence of flow direction on the steady state and dynamic performances of the cell. Among different flow directions, the coflow case is the most favorable for the planar SOFC, with improved performance. In response to a voltage step increase, the coflow case provides the most uniform transient behavior at different points of the cell. Despite the coflow direction, in which temperature dominates the slow dynamics of the local current density, in the low temperature regions of the counterflow and cross-flow cases, the slow dynamics of the current density tends to be characterized by the initial undershoot followed by a slower transient response that is due to the combined effects of the diffusion resistance within the porous electrode, hydrogen accumulation toward the fuel outlets, and the influence of the PEN temperature.